Hybrid Particleboard Made of Corn Husk (Zea Mays L.) and Sembilang Bamboo (Dendrocalamus Giganteus Munro): Effect of Adhesive Type and Particle Composition - Prasetiyo, Kurnia Wiji; Hermawan, Dede; Hadi, Yusuf Sudo; Subyakto, Subyakto; Firdaus, Muhammad; Syamani, Firda Aulya; Astari, Lilik (Universitas Negeri Semarang, 2021)
Particleboard is a panel product made of wood particles or other lignocellulosic materials added with adhesive then pressed. The development of particleboard manufactured using non wood biomass has become important due to the decreased of wood as main raw material for the particleboard industry. Corn husk (Zea mays L.) and Sembilang bamboo (Dendrocalamus giganteus Munro) are lignocellulosic biomass that has potential as renewable materials for hybrid particleboard. The purposes of this study were to determine the suitability, the effect of adhesive type, and particle composition on physical and mechanical properties of hybrid particleboard made of corn husk and Sembilang bamboo particles. The adhesive types used were urea formaldehyde (UF) and phenol formaldehyde (PF) with 10 wt% adhesive content and the composition of corn husk : Sembilang bamboo was set at 100 : 0, 75 : 25, 50 : 50, 25 : 75, 0 : 100 (% w/w). The target density of hybrid particleboard was set at 0.80 g/cm3. The boards were manufactured at 130 °C for UF and 150 °C for PF press temperature, 10 minutes and 2.5 MPa for the pressure of the hot press. The results showed that hybrid particleboard properties improved with increasing the amount of Sembilang bamboo particles in the board. Hybrid particleboard properties affected in ascending order were modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IB) and screw holding power (SHP). Generally, hybrid particleboard bonded PF adhesive has better properties than bonded UF adhesive. Results indicated that the addition of Sembilang bamboo particles in the mixture resulted in better properties of hybrid particleboard.